TANTANGAN PENDIDIKAN INDONESIA DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI ABAD 21 (Current Research in Education: Conference Series Journal, 2022)
21st century is a century of openness or era of globalization, meaning that human life in this century undergoes a different change from life in the previous century. In the 21st century, more emphasis or demand in creating the quality of human resources, this makes Indonesian education has challenges to improve quality human resources, grow, and be able to compete like the world citizens in the 21st century. the purpose of this research is to examine the factors that affect the quality of Indonesian Education that occurred in the 21st century and produce methods to be able to improve the quality of education that will produce quality human resources and have the competence of the 21st century. The method used in this research uses quantitative research method with survey approach and literature approach. Based on the results of research and discussion, it can be concluded that there are still several factors that cause the quality of human resources in Indonesia is still low and the need for component development to improve human resources in the field of education in the 21st century, namely the components of educators and students.